Secularism, Religion and Democracy. The democratic turn in the secularism-religion debate - Bermejo, Diego (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The revival of the religion in the new context of a global world-society, which is as modern as religious, doesn´t happen only as a sociological result of the dismantling of the postcolonial world —which denies the secularist forecast of the religion decline and provides the pluralism phenomenon with an unthought-of ethical and political complexity and virtuality—, but as a result of the modern reason crisis too, that makes reason rationally unable to justify political life relying on a rationalist ethical monism. The rationalist last foundation crisis affects as much the fundamentalist religious claims —which pretend to interpret the so called «religion resurgence or religion revival» in a «postsecular society» in a rapidly triumphal way, as the secularist claims which pretend to deny the religion any ethical and political virtuality in the public sphere. The democratic turn, antiauthoritarian and antidogmatic, coherently demanded within the context of the modern reason crisis by three wellknown representatives of the postmetaphysical, hermeneutical and pragmatist philosophy, such as Vattimo, Habermas and Rorty, replaces the debate between secularism and religion on the basis of true questions with the other on the basis of solidarity questions.
Keywords: secularism; religion; democracy; postmodernity; postmetaphysics; postsecularity; fundamentalism